2022
DOI: 10.3390/ijms232416168
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–Phenotype Association in ABCC2 Exon 18 Missense Mutation Leading to Dubin–Johnson Syndrome: A Case Report

Abstract: We report a case of a patient with Dubin–Johnson syndrome confirmed by a genetic study. A 50-year-old woman who had symptoms of intermittent right upper quadrant abdominal pain was diagnosed with calculous cholecystitis at another institute and was presented to our hospital for a cholecystectomy. She had no history of liver disease, and her physical examination was normal. Abdominal computed tomography showed a gallbladder stone with chronic cholecystitis. During a laparoscopic cholecystectomy for cholecystiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…They concluded that these autoantibodies to tumor-associated antigens may enhance the detection of HCC. Kim et al reported a patient with Dubin–Johnson syndrome, who had a missense mutation in exon 18 of adenosine triphosphate-binding cassette subfamily C member 2 (ABCC2) [ 13 ].…”
mentioning
confidence: 99%
“…They concluded that these autoantibodies to tumor-associated antigens may enhance the detection of HCC. Kim et al reported a patient with Dubin–Johnson syndrome, who had a missense mutation in exon 18 of adenosine triphosphate-binding cassette subfamily C member 2 (ABCC2) [ 13 ].…”
mentioning
confidence: 99%